2010
DOI: 10.1002/rcm.4710
|View full text |Cite
|
Sign up to set email alerts
|

Fluorous derivatization combined with liquid chromatography/tandem mass spectrometry: a method for the selective and sensitive determination of sialic acids in biological samples

Abstract: We have developed a novel method for selective and sensitive analysis of sialic acids (N-acetylneuraminic, N-glycolylneuraminic, and 2-keto-3-deoxy-D-glycero-D-galactonononic acid) utilizing liquid chromatography/tandem mass spectrometry (LC/MS/MS) combined with a fluorous derivatization technique. In this method, the carboxylic groups in the sialic acids are derivatized via amidation with heptadecafluoroundecylamine, a commercially available perfluoroalkylamine reagent. This reaction proceeds rapidly and read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 37 publications
(46 reference statements)
0
20
0
1
Order By: Relevance
“…MS is well suited for the detection because of its high sensitivity and selectivity. However, carboxylic acids tend to be poorly ionized by the ionization sources used in MS. To enhance the detection of carboxylic acids in ESI-MS/MS, several chemical derivatization procedures suitable for the positive ion detection have been developed [71][72][73][74][75][76]. For example, Cartwright et al reported that tris(2,4,6-trimethoxyphenyl)phosphonium propylamine (TMPP) bromide was used as the derivatization reagent for the LC-ESI-MS/MS analysis of carboxylic acids in pharmaceutical products [75].…”
Section: Carboxylic Acidsmentioning
confidence: 99%
“…MS is well suited for the detection because of its high sensitivity and selectivity. However, carboxylic acids tend to be poorly ionized by the ionization sources used in MS. To enhance the detection of carboxylic acids in ESI-MS/MS, several chemical derivatization procedures suitable for the positive ion detection have been developed [71][72][73][74][75][76]. For example, Cartwright et al reported that tris(2,4,6-trimethoxyphenyl)phosphonium propylamine (TMPP) bromide was used as the derivatization reagent for the LC-ESI-MS/MS analysis of carboxylic acids in pharmaceutical products [75].…”
Section: Carboxylic Acidsmentioning
confidence: 99%
“…The mono-fluorous derivatives were obtained by derivatization of monoamines [n-butylamine (C 4 ), nhexylamine (C 6 ), and n-octylamine (C 8 )] with STFN using the procedure described for polyamines in section 2.2. On the other hand, to prepare the corresponding non-fluorous dialkyl-to tetraalkylated derivatives, the polyamines were derivatized with n-nonanoic acid (which has the same carbon number as STFN) in the presence of the condensation reagent, 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)4-methylmorpholinium chloride (DMT-MM) with previously reported procedure [20]. These mono-fluorous and non-fluorous derivatives were analysed by selected ion monitoring mode in the positive ESI mode.…”
Section: Comparative Studymentioning
confidence: 99%
“…Utilizing such fluorous affinity, we reported that accurate and precise LCtandem mass spectrometric (MS/MS) analysis of biogenic compounds could be performed following derivatization with a fluorous-tag reagent [20][21][22]. Because the obtained perfluoroalkyl (fluorous) derivatives could be completely separated from non-fluorous species, such as endogenous components in the biological matrix, on the fluorous LC column, this method did not require further sample pretreatment to eliminate matrix-induced effects in MS/MS detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have used stable isotope-labeled internal standards to overcome matrix effects, although the use of such internal standards, especially for deuterized ones, is sometimes limited because of unexpected behavior, such as different recoveries or retention times, during pretreatment or LC separation [13,14]. On the other hand, our developed separation-oriented derivatization method using fluorous affinity is useful for eliminating matrix effects because non-fluorous matrix components are formerly eluted and clearly separated from the fluorous derivatives by fluorous LC [15,16]. We applied this method to the accurate analysis of trace amounts of biogenic primary amines [DA, NE, 3-methoxytyramine (3-MT), normetanephrine (NM), tyramine (Tyr), 5-HT, tryptamine (Tryp), 5-methoxytryptamine (5-MT), and histamine (Hist)] in human plasma samples [17].…”
Section: Selective Analysis Of Biogenic Primary Amines Using Lc-ms/msmentioning
confidence: 99%